2021
DOI: 10.1186/s13104-021-05661-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of probiotic as add-on therapy with conventional therapy and alone in malaria induced mice

Abstract: Objective Chloroquine is used as a conventional drug therapy for the treatment of malaria. The existence of resistance to chloroquine shown among various species of Plasmodium leads to the search for more efficacious therapy to treat malaria. Probiotic (Lactobacillus casei) has been tried as an add-on therapy with chloroquine. Probiotics are ingested microorganisms associated with a beneficial effect on humans and other species. The study was done to check the efficacy of L. casei as an add-on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Preclinical research on targeted microbiome alterations is shown in Table 5 [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 ]. The range of these studies presages where Microbiome First Medicine is headed.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…Preclinical research on targeted microbiome alterations is shown in Table 5 [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 ]. The range of these studies presages where Microbiome First Medicine is headed.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…15 However, another study performed by Mahajan in 2021 investigating the effect of probiotic L. casei as adjuvant therapy in P. berghei infected C57BL/6 mice showed contrasting results, where L. casei and chloroquine combination resulted in complete suppression of parasitemia level. 8 A study investigating probiotics as pretreatment showed that P. chabaudi infected mice had lower parasitemia compared to control group. In this study, oral administration of L. casei was likely to form a successful colonization and bacterial adhesion in the intestinal tract, which then affected the immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another study from Mahajan et al, that observed the effect of L. casei probiotic as adjuvant therapy with chloroquine in C57BL/6 mice infected with P. berghei, showed that the combination of L. casei and chloroquine resulted in a suppression of the degree of parasitemia. 8 Dysbiosis due to Plasmodium infection could affect intestinal immune response, abnormal cytokine production, and the severity of malaria. This condition aids in polarization of macrophages and dendritic cells (DCs), inducing T helper 1 (Th 1) and Th17 cells to produce proinflammatory cytokines, such as IL-6, IL-12, TNF-α, interleukin (IL)-1β, and IFNγ.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated approaches to restore a healthy microbiota composition in the gut and reduce the severity of Plasmodium infection. 31,55 A probiotic diet containing Lactobacillus and Bifidobacterium was shown to reduce parasitemia, indicating the role of microbiota to fight Plasmodium infection by modulating the gut mucosal immune response. 6,29 Lactobacillus also know to reduce the infection at lower respiratory tract that cause neonatal sepsis, 56 while Bifidobacterium showed protective effect against Clostridium difficile 57 and Klebsiella pneumonia 58 infections.…”
Section: Dysbiosis and Malaria Severitymentioning
confidence: 99%